Institutional capacity for designing and implementing agricultural and rural development policies and strategies in Nigeria - Adebayo, Kolawole; Babu, Suresh Chandra; Rhoe, Valerie (International Food Policy Research Institute, 2010)
An agricultural system consists of production, processing, storage, marketing, extension, research, and training. While production is a result of land, labor, capital, and entrepreneurship, its magnitude and efficiency from the farm to the consumer depend on handling, preservation, and the processes of making the products readily available and conveniently consumable, which are directed by government policies. For this reason, good institutional capacity for designing and implementing agricultural and rural development policies is critical for a successful agricultural system, and ultimately for food security. This brief highlights key issues on the capacity for designing and implementing agricultural and rural development policies, strategies, and programs in Nigeria.